The Influence of Internet Marketing on Purchase Intention in E-Commerce Blibli - Yuliarti Maghfira Annahli; Agus Rahayu; Puspo Dewi Dirgantari (Administrasi Bisnis Indonesia, 2024)
This research is a quantitative study that examines social phenomena with the aim of knowing the effects of internet marketing on purchasing intentions. The population of this study is Blibli consumers. This study took a sample of 100 respondents through non -probability sampling techniques for purposive sampling methods. Data collection in this study in the form of distributing questionnaires to users and those who have shopped using the Blibli site. The data analysis technique used is descriptive analysis and inferential analysis with data processing calculation analysis tools using partial least square (PLS) applications. After analyzing the data, the results show that there is a positive and significant influence on the internet marketing variable on the intention of purchasing.